Social responsibility in the technological sector: A look at the ethical commitment of professionals in Information Technologies - Padrón, Nildred; Polanco, Norailith (Impacto Científico, 2022)
The purpose of this article is to make approximations about the term of Social Responsibility as an effective strategy for the alignment of the ethical commitment that defines the professional in technology, based on the coexistence and relationship with the community and sustainable environments. Theoretically, this document is based on the ideas of Miquilena (2018), Varela and Egea (2009), Vallejo (2012), Pacheco (2015), OIT (2007), López (2004), Paz and Miquilena (2014), Compromiso RSE (2018), González and Mayz (2008), González and Jaén (2006). The research methodology is Documentary - Bibliographic, collecting and reviewing from primary sources such as magazines, texts and queries in different electronic materials. The general conclusions of this research allow providing approaches related to the dynamics that must be carried out from the technological sector to meet the codes, regulations, values and moral ideals that characterize the cultural integration in productive processes within historical and social contexts, to continue optimizing the professional performance and improvement of living standards.